The international legal order 1919–2019. (June 2019) - Nardin, Terry
Despite repeated claims during the past century that the international legal order has been radically transformed, the contours of that order are in many ways the same in 2019 as they were in 1919. New laws govern international institutions, human rights, trade, and the environment and new institutions have emerged that affect how international law is interpreted and applied. War has lost legitimacy as a tool of foreign policy and individual responsibility for aggression and crimes against humanity has been affirmed. Yet these changes build on ideas and practices that may have been rudimentary but were not absent a century ago. Underlying them are persistent differences involving a shifting cast of old and new states as well as differences between local and universal ideals and between instrumental and noninstrumental conceptions of law. The traditional understanding of state sovereignty on which the international legal order rests has been qualified but not discarded, and its persistence confirms that the system it orders remains a system of states.